Teeth Whitening and Antibacterial Effects of Juglans regia Bark: A Preliminary Study - Riham Al-Rawi; Yusra Bashir; Aseel Mustafa; Mennatalla Omar; Noor AL-Rawi; Musab Saeed; Asmaa Uthman; Natheer H. Al-Rawi (Hindawi Limited, 2021)
Objectives. Natural folk medicines with antimicrobial effects have been under investigation during the past decades. The aim of this study was to evaluate the teeth whitening and antimicrobial effects of ethanol extract of Persian walnut "Juglans regia" barks. Materials and Methods. Minimum inhibitory concentration (MIC) was determined using a broth microdilution assay which was conducted through a 2-fold serial dilution method, and a whitening experiment was done in vitro on extracted teeth, with a pH test being performed on 2-fold dilutions of the ethanol extract. Result. It was found that the MIC for Enterobacter and E. coli and Staphylococcus and Pseudomonas was found to be 5 mg/ml and 2.5 mg/ml, respectively. Both dilutions were found to be acidic, and the extract of Juglans regia bark also demonstrated the ability of teeth whitening. Conclusion. This study supports the use of Juglans regia bark as a natural product in dentistry because of the confirmed antimicrobial ability as well as its whitening effect. Clinical Relevance. Herb extract might be incorporated within commercially available kinds of toothpaste to enhance its whitening and antimicrobial effects.